5(3t+1)+2=5(1+3t)

Simple and best practice solution for 5(3t+1)+2=5(1+3t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3t+1)+2=5(1+3t) equation:



5(3t+1)+2=5(1+3t)
We move all terms to the left:
5(3t+1)+2-(5(1+3t))=0
We add all the numbers together, and all the variables
5(3t+1)-(5(3t+1))+2=0
We multiply parentheses
15t-(5(3t+1))+5+2=0
We calculate terms in parentheses: -(5(3t+1)), so:
5(3t+1)
We multiply parentheses
15t+5
Back to the equation:
-(15t+5)
We add all the numbers together, and all the variables
15t-(15t+5)+7=0
We get rid of parentheses
15t-15t-5+7=0
We add all the numbers together, and all the variables
2!=0
There is no solution for this equation

See similar equations:

| 2(x-3)=4x-6-2x | | x-116-30=180 | | -.25(x–4)=10+.5(x–3) | | 464=n-270 | | 1/3(6y-9)=-2y-3 | | 2(u+3)=6 | | 5n-3n-6=n+6 | | 10x-2=10x+7 | | 11−2x+4=−1 | | 3(2-5x)=66 | | 4x+24=-3x-60 | | 550+30x=2,500 | | -3.1m-1.42=-12.5m+8.93-11.3m | | 4x-1+(2x^2+3)=0 | | 49-15+7g=90 | | -3y+16=-5 | | -9w=-10w-18 | | 23+3x=3(x+8) | | -(10x+6-2)=78 | | A(x)=4x^2+400/x | | 400=6x−20 | | x^2+15x+43=0 | | -(1+5b)-3=14-8b | | -50=-10-10e | | (6x-2)+15=7x+6 | | -(u-6)=0 | | -16+5n=-7(-6+8n+3 | | x/2-3x/4+5x/6=15 | | -34=6-4c | | -6x+11=47 | | 2f=42 | | 4j=–5j−9 |

Equations solver categories